Anti Fraud Strategy Evaluation in Bank XYZ - Andri Satria Himawan; Dodik Siswantoro (Peneliti.net, 2023)
Fraud that occurred in Indonesia in 2019 reached a total of 239 cases with a total loss of IDR873.43 billion, in which the average loss per case was IDR7.24 billion. Bank as a company engaged in the financial services sector has a high risk of fraud and need an adequate internal controls to manage fraud risk. Regulation No. 39/POJK.03/2019 concerning the implementation of an anti-fraud strategy at commercial banks which contains 4 pillars in controlling fraud risk. Fraud incidents at Bank XYZ over the last 5 years tend to increase and potentially have a negative impact on its reputation and operational activities. Due to these incidents, this research will focus on evaluating the implementation of anti-fraud strategies as well as in-depth evaluating effectiveness of the implementation that have not been maximized. This research conducted in qualitative methods and took a case study approach with data collection methods through both document studies and interviews, whilst the analysis adopted criteria according to applicable OJK regulations. The implementation of the anti-fraud strategy at Bank XYZ has met the specified criteria, nonetheless the monitoring, evaluation and follow-up pillars have not been implemented according to the criteria, so these pillars have not been effective.